Evaluación de las fases de pasteurización, retención de caseína-grasa y penetración de la cuajada para la estandarización del proceso de queso pasta hilada tipo hoja - Vera Guzmán, Frank Michael (2016)
The present study is focused on the evaluation of the pasteurization, casein-fat retention and curd penetration phases in order to show the effect in the process of the leaf-spinning cheese, through the appreciation of the physic-chemical characteristics of the product, Optimizing the same and characterizing physicochemical and sensorially the product resulting from such optimization. In order to denote the effect, a three-level Box-Behnken response surface factor plan was used, obtaining pasteurization temperature between 65°C and 68°C, penetration between (1,9cm and 2,3cm) and retention between (10 minutes and 30 minutes ). The sensorial characterization was done through a descriptive analysis and textural profile with a panel of semenresident scavengers. The effect of pasteurization temperature on moisture and retention on acidity, fat and moisture was determined, while no effect of retention was observed in the process, obtaining the optimization point at pasteurization temperature of 67,997ºC with Penetration of 1,9 cm and 21,3727 min of retention. The cheese obtained in the optimization complies with rules of cheeses and similar characteristics in its composition to other cheeses of the same family, described by the scavengers with an intermediate milk smell, low salt level, with moderate creaminess, medium hardness to the touch, Low oiliness, intermediate ivory odor, moderate sweetness and low bitterness, while in the textural profile the scavengers denoted values close to the intermediate in firmness, elasticity, adhesion, friability, chewability and solubility and near low deformity and granularity.